A palynological survey of the genus Iberis (Brassicaceae), known as candytufts, in Turkey - Yilmaz Çitak, Burcu (Phytotaxa, 2019)
The present study reports for the first time detailed palynological traits of the Turkish species Iberis. Both light microscope (LM) and scanning electron microscope (SEM) were used for the characterisation of the species. Radially symmetrical, isopolar, and tricolpate pollen grains were observed as common characters in all of the examined taxa. The pollen grains were prolate-spheroidal with polar axes ranging from 21.97 to 29.25 µm and equatorial axes ranging from 20.34 to 26.09 µm. Their polar shapes were subcircular to subtriangular. Two types of exine ornamentation were observed using a SEM. A numerical UPGMA analysis showed that the dimensions of polar axes, equatorial axes and outline in polar view (amb) were the most valuable variables for separating the Iberis species.